Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide. Issue 22 (1st November 2019) - Trumbo, Daryl R.; Salerno, Patricia E.; Logan, Kenneth A.; Alldredge, Mathew W.; Gagne, Roderick B.; Kozakiewicz, Christopher P.; Kraberger, Simona; Fountain‐Jones, Nicholas M.; Craft, Meggan E.; Carver, Scott; Ernest, Holly B.; Crooks, Kevin R.; et al.
Abstract: Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12, 000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.